Optically Active Polymers A Systematic Study on Syntheses and Properties - Dutta, Pradip K.; Kumar, Vinod; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
The brief presents a systematic study of synthesis of optically active polymers. It discusses in detail about the synthesis of three different types of optically active polymers from helical polymers, dendronized polymers and other types of polymeric compounds. The brief also explains the synthesis of optically active azoaromatic and carbazole containing azoaromatic polymers and copolymers; optically active benzodithiophene; and optically active porphyrin derivatives. The final chapter of the brief discusses different properties of optically active polymers such as nonlinear optical properties, chiroptical properties, vapochromic behavior, absorption and emission properties, fabrication, and photochromic properties. The intrinsic details of different properties of optically active polymers presented in this work will be useful for researchers and industry personnel, who are actively engaged in application oriented investigations.
Chapter 1. Introduction -- Chapter 2. Synthesis of optically active polymers -- Chapter 3. Properties -- Chapter 4. Conclusion -- Chapter 5. References.
Keywords: Polymers; Bioorganic chemistry; Biotechnology; Polymers; Bioorganic Chemistry; Chemical Bioengineering